Design of Self-service Car Washing Machine Control System Based on ARM. (August 2020) - Peng, Sun
Abstract: With the cars in our country's rapid increase, the limited quantity of traditional car washing shop has been unable to satisfy people's needs. Responding to this problem the author designed a set of self-service car washing machine control system based on ARM, and a set of remote monitoring system based on 4G mobile network. The terminal control system adopted high speed, low power microcontroller LPC4350 as the control core; adopted RFID read-write module to realize IC card consumption; adopted EM770W 4G module for the washing machine terminal could connect to 4G mobile network. Through MODBUS protocol, the remote monitoring system based on KINGVIEW6.55 could communicate with the terminal system, and realized the real-time monitoring and recording the washing machines' working parameters regularly. Because the designed system realized the unattended self-service washing, so it greatly reduced the maintenance workload, and improved the work efficiency.